The duel : the parallel lives of Alexander Hamilton & Aaron Burr - St. George, Judith, 1931- (Speak, 2016)
Highlights similar aspects of the lives of Alexander Hamilton and Aaron Burr, and examines how the two war heroes and founding fathers ended up in a duel that cost one of them his life.